Biomass derived fabrication of a novel sea cucumber-like LiMn2O4/C composite with a hierarchical porous structure as the cathode for lithium-ion batteries. (10th January 2016) - Wang, Jifei; Liu, Wei; Liu, Shuang; Chen, Jiaxin; Wang, Huanlei; Zhao, Shuping
Graphical abstract: Highlights: Sea cucumber-like spinel LiMn2 O4 /C composites have been successfully synthesized. The unique structure is aggregated by inner nanocrystals and outer microcrystals. The LiMn2 O4 /C composites exhibit excellent electrochemical performances. Abstract: Biological microstructures display an unparalleled degree of complexity that can be employed as templates to create exquisite architecture of metal oxides in the burgeoning field of materials. In this work, sea cucumber-like LiMn2 O4 /C composites aggregated by nano-/micro-crystals have been fabricated via a facile biotemplating method using commercial spirulina as sacrificial templates and a simple carbon coated approach. The structure and morphology of the as-obtained products are characterized with X-ray diffraction (XRD) and electron microscopy (SEM and TEM) techniques. The electrochemical test indicates that these unique LiMn2 O4 /C composites possess the excellent capacity retention and rate property, and the reversible discharge capacity can retain 94% of its initial capacity after 200 cycles at a rate of 10 C. The performance improvement may be attributed to the Li + rapid diffusion in the hierarchical porous structure, and the excellent electron transport of carbon coating as well as their barrier effect for the manganese ions dissolution in cycling.